Varying Vector Pulse Width Modulation for Three Phase Inverter - Raju J; Kowsalya M (Bulletin of Electrical Engineering and Informatics, 2014)
This paper mainly deals with designing a control scheme to eliminate the OFF STATE (T0 state) present in a Space Vector Pulse-Width Modulation; this has been achieved by redesigning the equations for calculating the reference vector of modulating signal (Vref). In widely used Space Vector Pulse Width Modulation Vmax of carrier signal is greater than Vref of modulating signal (except when Vref = Vmax). Thus during this state the drive goes into the OFF STATE (T0 state). T0 States are similar mirror image states; hence they have no good or bad effect on the system. But there is an amount of switching loss occurring when the switch executes the T0 state. The new equations for reference vector resulted in reducing the switching losses to half the actual value. Also it has various other advantages like. Increase in DC-Link utilization from 15.47 to 21.14 at 2 KHz carrier frequency and Reduction in THD of the system compared to widely used SVPWM.